Avaliação de alterações orais em pacientes submetidos a transplante de medula óssea - Lima, Emeline das Neves de Araújo (2010)
Bone marrow transplantation (BMT) is currently the best therapeutic option for patients with hematologic diseases, solid tumors or autoimmune disorders. It is characterized by intravenous infusion of hematopoietic stem cells in order to restore marrow function. However, this procedure requires concomitant immunosuppression treatment, which favors the development of certain complications, often manifested in the oral cavity. This study aimed to evaluate the incidence of oral changes in patients undergoing BMT and to correlate these results with clinical aspects related to the patients and the transplants performed. This is a prevalence study, with cross-sectional design, carried out in a BMT service at the Institute of Onco-Hematology of Natal (ION) and Natal Hospital Center. Data collection was based on questionnaires, clinical examination of the oral cavity and consultation in the medical records. The sample consisted of 51 patients undergoing BMT. After the analysis, was found a general status with good health conditions and presence of oral changes in about half of patients who composed the sample. The manifestations observed were, in decreasing order of frequency: mucositis; gingival alteration and thrombocytopenic purpura; mucosal pigmentation; lichenoid reaction and candidiasis. The oral changes were observed more frequently in cases of allogeneic TMO, in different periods post-transplant, without significant differences related to the source of cells. It was found statistically significant association between the presence of graft-versus-host disease (GVHD) and oral changes (p < 0,001). Therefore, it is concluded that there is a relatively high incidence of changes in oral cavity of patients receiving bone marrow transplantation, a fact which confirms the need to consider this site for examination, diagnosis, treatment and prognosis of possible complications of BMT